DAMPAK PARIWISATA SUMURJOMBLANGBOGO TERHADAP PEREKONOMIAN MASYARAKAT - Siti Nur Kholifah; Hendri Hermawan Adi Nugara (Bapperida Kabupaten Pekalongan, 2023)
His research was conducted in the village of sumurjomblangbogo, Bojong District, Pekalongan Regency. The purpose of this study was to find out how the impact of the existence of the new tour of the Tirta Arum swimming pool in the village of sumurjomblangbogo on the economy and the government of local residents. his type of research is descriptive qualitative research with data sources obtained through observation and field interviews. From the results of this study, it can be concluded that the existence of a new tour of the Tirta Arum swimming pool in the village of sumurjomblangbogo has a positive impact on the economy of the government and local residents. The impact resulting from the existence of Tirta Arum swimming pool tourism is in the economic field, namely as a forum for opening up business fields for local residents.